Fatality of Cases by New Coronavirus Disease (COVID 19): A Case Study in the Mexican State of Guanajuato - Navarro-Olivos, Efrain; Flores-Vargas, Gilberto; Gallardo-Luna, Maria de Jesus; Magos-Vazquez, Francisco Javier; Diaz-Martinez, Daniel Alberto; Padilla-Raygoza, Nicolas (New Horizons in Medicine and Medical Research Vol. 9, 2022)
The objective of this study is to describe the epidemic and report of fatality of confirmed cases of COVID-19 in the Mexican state of Guanajuato, until October 2, 2020. This analysis was based on the National Epidemiological Surveillance System Database from Mexico. Age, sex, comorbidities (diabetes, chronic obstructive pulmonary disease, asthma, hypertension, cardiovascular disease, immunosuppression, chronic renal disease, obesity, and smoking), date of death, and results of real-time reverse transcription polymerase tests were all obtained. Case Fatality Ratio, Chi-squared test, and P-value were employed in statistical analysis to highlight connections between variables. The influence of comorbidities on death due to COVID-19 was shown using the odds ratio and confidence intervals at 95 percent. A Bayesian network model was also used to determine the statistical dependencies between risk factors, comorbidities, and death. There were 100,109 suspected cases, with SARS-CoV-2 testing positive in 41.69 percent of them. COVID-19 found that being over 60 and male had a greater impact on fatality. In Guanajuato state, 1,457 (48.68%) of deaths occurred in Mexican Institute of Social Security, with a case fatality ratio of 15.63%; meanwhile, in the Ministry of Health from Guanajuato State occurred 1,260 (42.10%) of the deaths with a case fatality ratio of 4.14%. Diabetes (OR 5.16, CI95% 4.77–5.59), chronic obstructive pulmonary disease (OR 6.34, CI95% 5.37–7.49), immunosuppression (OR 2.85, CI95% 2.17–3.76), cardiovascular disease (OR 4.20, CI95% 3.51–5.02), hypertension (OR 4.74, CI95% 4.39–5.11), chronic kidney disease (OR 6.27, CI95% 5.30–7.42), obesity (OR 1.87, CI95% 1.72–2.03), and smoking (OR 1.60, CI95% 1.41–1.81) had effect on death by COVID-19. The biggest risk factors for death among COVID-19 patients in Guanajuato were age and sex. Diabetes, chronic obstructive pulmonary disease, immunosuppression, cardiovascular disease, chronic renal disease, obesity, and smoking, on the other hand, are all risk factors for death. Comorbidities and risk factors, on the other hand, are substantially associated. HIV/AIDS has no effect on SARS-CoV-2 illness lethality, although asthma appears to be protective.